1992
DOI: 10.1590/s0074-02761992000900023
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of immune protection in the asexual blood stage infection by Plasmodium falciparum: analysis by in vitro and ex-vivo assays

Abstract: Mechanisms of immune protection against the asexual blood stage infection by Plasmodium falciparum are reviewed. Recent studies of two independent lines of research developed at the Institut Pasteur, in humans and primate infections clearly indicate an obligatory interaction of antibodies and effector cells to express the anti-parasitic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The mechanisms involved in protective immunity, either clinical or anti-parasite, remain poorly understood for vivax malaria. Antibody-dependent immune responses are considered the basic mechanism of anti-parasite immunity in P. falciparum infections (Cohen et al 1961, Fandeur et al 1984, Bouharoum-Tavoun et al 1990, Groux et al 1990, Gysin et al 1992). However, no equivalent observations are available for P. vivax and how anti-parasite immunity develops against P. vivax remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in protective immunity, either clinical or anti-parasite, remain poorly understood for vivax malaria. Antibody-dependent immune responses are considered the basic mechanism of anti-parasite immunity in P. falciparum infections (Cohen et al 1961, Fandeur et al 1984, Bouharoum-Tavoun et al 1990, Groux et al 1990, Gysin et al 1992). However, no equivalent observations are available for P. vivax and how anti-parasite immunity develops against P. vivax remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Humans living in endemic areas gradually develop broad antibody repertoires to malarial antigens as they age, which is correlated with decreased severity of disease symptoms [16, 41]. This is particularly true when comparing antibody responses between uncomplicated malaria and severe malaria patients [42] as well as those comparing asymptomatic and symptomatic malaria patients.…”
Section: Discussionmentioning
confidence: 99%
“…Early experiments established that passive transfer of immune sera to naïve individuals drastically reduced symptoms of acute infection indicating that antibodies played a central role in premunition [40, 80, 81]. Later it was shown that this immunological phenomenon required cooperation between antibodies and monocytes in order to be effective [41, 82, 83]. Patient data from Malawi has recently demonstrated that in patients with severe malaria, monocytes have decreased expression of activation markers compared to those from patients with uncomplicated malaria, underscoring the role that activated monocytes play in controlling morbidity [64].…”
Section: Discussionmentioning
confidence: 99%
“…Purified human hyperimmune gamma globulins prepared from West African hyperimmune adults and protective in passive transfer assays in humans (HIG 1 ) (25) were kindly provided by P. Druilhe. These Igs were also efficient at clearing infections of Saimiri monkeys with the FUP/SP-O parasites (12). The activity on R parasites has not been tested in passive transfer assays.…”
Section: Methodsmentioning
confidence: 99%